Effectiveness Of Early Ambulation with Indigenously Prepared Harness Sling on Functional Independence in Incomplete Spinal Cord Injury - Kanase, Suraj B.; Adhikari, Akshata; Tanishqa C, Tanishqa C (Journal of Neonatal Surgery, 2025)
Purpose of the study: Spinal cord injury (SCI) refers to damage to the spinal cord caused by either traumatic events, such as falls or road traffic accidents, or non-traumatic factors, including tumors, degenerative diseases, vascular disorders, infections, toxins, or congenital anomalies. The higher the injury on the spinal cord, the more extensive the disability, ranging from quadriplegia in cervical injuries to paraplegia in thoracic or lumbar injuries. These neurological deficits significantly impact daily functioning and often necessitate multidisciplinary rehabilitation. Thus, this study aimed to assess the effectiveness of early ambulation using an indigenous prepared harness to enhance ambulation among SCI patients. Methodology: A total of 30 patients were included in the study. The inclusion criteria were patients with incomplete SCI, aged between 20-50 years, and paraplegic or quadriplegic patients. 30 participants were allotted by purposive sampling technique. Each allotted participant was given rehabilitation for 45 mins- 1 hr. Analysis: The analysis was done using the SPSS software. The SCIM III and WISCIM II were the outcome measures used to assess the participant's pre and post-study. Results: The result of the study indicated significant improvement in both the outcomes post the study with p value being 0.01 for SCIM III and a p-value being 0.002 for WISCIM II. Conclusion: The study concluded that indigenously prepared harnesses used for incomplete SCI patients proved to be effective in enhancing early ambulation and locomotor training.